Девочка из города - Воронкова Любовь Федоровна (Школьная программа, 2017)
Экземпляры: ф.15 (2021) / Инвентарный номер: 56744 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 75 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6